The Effect of Product Quality, Price, and Promotion on iPhone Smartphone Purchase Decisions with Brand Image as a Moderating Variable (A Study of Generation Z STIESIA Surabaya in 2025) - Yusup Prasetyo Wicaksono; Budiyanto Budiyanto (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study examines the impact of product quality, price, and promotion on iPhone purchasing decisions among STIESIA Surabaya Z-generation students, with brand image serving as a moderating variable. Furthermore, the study employs a quantitative approach, specifically a survey. The data was collected using purposive sampling. In accordance with this, 134 respondents were chosen because they matched the criteria for validity or reliability as samples. Moreover, the data analysis technique used was Structural Equation Modelling Partial Least Squares (SEM-PLS). The evaluation results in the measurement model indicate that all constructs met the criteria. Meanwhile, structural model evaluation indicates that the model describes effectively. Additionally the hypothesis test found that price has a positive and significant impact on purchasing decisions. However, both product quality and promotion have insignificant effects. In addition, brand image increases the influence of product quality while decreasing the effect of price. Unfortunately, it does not considerably moderate the effect of promotion. The findings lead to the conclusion that Z-generations' purchasing decisions for premium products are driven more by perception of value and brand image than functional qualities and promotion.